2016
DOI: 10.1063/1.4940429
|View full text |Cite
|
Sign up to set email alerts
|

In vitro methods to study bubble-cell interactions: Fundamentals and therapeutic applications

Abstract: Besides their use as contrast agents for ultrasound imaging, microbubbles are increasingly studied for a wide range of therapeutic applications. In particular, their ability to enhance the uptake of drugs through the permeabilization of tissues and cell membranes shows great promise. In order to fully understand the numerous paths by which bubbles can interact with cells and the even larger number of possible biological responses from the cells, thorough and extensive work is necessary. In this review, we cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 200 publications
(261 reference statements)
0
63
0
Order By: Relevance
“…The OptiCell TM (Nunc, Thermo Fisher Scientific, Wiesbaden, Germany) has been extensively used for both microbubble characterization and drug delivery studies [3]. Since the OptiCell is no longer being manufactured, the CLINIcell R (MABIO, Tourcoing, France) is an interesting alternative imaging and cell culture chamber.…”
Section: Introductionmentioning
confidence: 99%
“…The OptiCell TM (Nunc, Thermo Fisher Scientific, Wiesbaden, Germany) has been extensively used for both microbubble characterization and drug delivery studies [3]. Since the OptiCell is no longer being manufactured, the CLINIcell R (MABIO, Tourcoing, France) is an interesting alternative imaging and cell culture chamber.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve these aims, we rely on well-known analytical models that reproduce the observed fluid flow in very good approximation. Our results show that flow measurements can be used as diagnostics for the bubble dynamics which could additionally lead to optimization of the energy delivered to the system in real applications (Fernandez Rivas et al 2010;Verhaagen 2012;Lajoinie et al 2016). The precise determination of the different bubble oscillation regimes (linear, nonlinear, bubble emission) could allow for considerable energy savings, and a significant enhancement in control and reliability of processes.…”
mentioning
confidence: 99%
“…[26][27][28] Zhou et al showed that the impact of the microbubble on the membrane permeability decreased dramatically with increasing distance between the cell and the bubble. [26][27][28] Zhou et al showed that the impact of the microbubble on the membrane permeability decreased dramatically with increasing distance between the cell and the bubble.…”
Section: Introductionmentioning
confidence: 99%